Interactive English vocabulary mobile games for UiTM pre-diploma students / Mohd Farid Jamaludin, Mohd Nizam Osman and Nor Arzami Othman - Jamaludin, Mohd Farid; Osman, Mohd Nizam; Othman, Nor Arzami (UiTM Cawangan Perlis, 2018)
Knowing that education is a part of important element in economic growth, this research was focused on the development of interactive mobile game specifically to create vocabulary related to idioms for young learners of English. The major concern among Pre-Diploma students is their lack of English vocabulary despite years of learning the subject. Therefore, this has affected their confidence level whenever they are required to use English either in spoken or written communication. We investigate the effect of mobile games on learning targeted vocabulary for Pre-Diploma students. Moreover, this study also examines whether the interactive mobile games created can improve motivation to learn and foster a deeper processing of vocabulary especially in terms of idioms for young learners of English. Therefore, through the mobile game, students will be exposed to the benefits of technology development nowadays. Lecturers also can opt for a more interactive way of teaching vocabulary rather than relying on the traditional methods alone. The functional testing and usability test have been conducted by the expert and real users to ensure that the project delivered meets the objectives. This project was developed using GameSalad that and published to the mobile with Android platform. Expected outcome was achieved after experiment conducted.